2015
DOI: 10.4049/jimmunol.1402260
|View full text |Cite
|
Sign up to set email alerts
|

CD28 Promotes Plasma Cell Survival, Sustained Antibody Responses, and BLIMP-1 Upregulation through Its Distal PYAP Proline Motif

Abstract: In health, long-lived plasma cells (LLPC) are essential for durable protective humoral immunity, and conversely in disease are a major source of pathogenic antibodies in autoimmunity, graft rejection and allergy. However, the molecular basis for their longevity is largely unknown. We have recently found that CD28 signaling in plasma cells (PC) is essential for sustaining antibody titers, by supporting the survival of LLPC but not short-lived PC (SLPC). We now find that unlike SLPC, CD28 activation in LLPC indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 52 publications
(101 reference statements)
3
46
0
1
Order By: Relevance
“…Nevertheless, we observed a trend towards a more rapid decline the DSA at day 42, raising the possibility that CTLA4-Ig may inhibit antibody production by plasma cells (Fig 1B). Indeed, Lee and colleagues [41, 42] have reported that long-lived plasma cells resident in the bone marrow require CD28-B7 interactions for their survival. Thus, a more careful analysis of the impact of CTLA4-Ig on long-lived plasma cells is required, as there continues to be a strong clinical need to identify drugs that can reverse established DSA responses.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we observed a trend towards a more rapid decline the DSA at day 42, raising the possibility that CTLA4-Ig may inhibit antibody production by plasma cells (Fig 1B). Indeed, Lee and colleagues [41, 42] have reported that long-lived plasma cells resident in the bone marrow require CD28-B7 interactions for their survival. Thus, a more careful analysis of the impact of CTLA4-Ig on long-lived plasma cells is required, as there continues to be a strong clinical need to identify drugs that can reverse established DSA responses.…”
Section: Discussionmentioning
confidence: 99%
“…4 The signals downstream of CD28 activation have been thoroughly investigated in T cells; however, the downstream mediators in plasma cells are only beginning to be characterized. [5][6][7] CD28 is expressed in the subset of bone marrow cells to which the most long-lived fraction of human plasma cells belong 8 and has been reported to be a poor prognostic indicator for patients with myeloma. It is highly expressed at diagnosis in patients with MAF translocations, and expression correlates with disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In addition, in a dual therapy setting including bortezomib, belatacept suppressed memory B cell proliferation. 7,8 Furthermore, studies in healthy human volunteers demonstrated CD28 expression on approximately 30% of LLPC. Interestingly, murine studies revealed that CD28 is important for LLPC survival and maintenance of long-term antibody titers.…”
mentioning
confidence: 99%
“…Interestingly, murine studies revealed that CD28 is important for LLPC survival and maintenance of long-term antibody titers. 7,8 Furthermore, studies in healthy human volunteers demonstrated CD28 expression on approximately 30% of LLPC. 9 Finally, recent studies revealed decreased production of de novo donor-specific HLA antibodies (DSA) 10,11 and elimination of preexisting DSA 12 in minimally sensitized recipients treated with belatacept compared to those patients treated with cyclosporine.…”
mentioning
confidence: 99%